2019
DOI: 10.1515/iss-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation, making patients fit for surgery – a new frontier in perioperative care

Abstract: Optimizing a patients’ condition before surgery to improve the postoperative outcome can be achieved by using prehabilitation; preoperative interventions focusing on modifiable risk factors to improve the physical, nutritional, and mental status of the patient. A multimodal, multidisciplinary approach induces a synergistic effect between the various interventions and affects the outcome postoperatively. While awaiting higher-quality evidence, the worldwide implementation of prehabilitation programs has started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
1
17
0
2
Order By: Relevance
“…Multimodal prehabilitation programs are increasingly implemented into standard care ( 4 ) and a multimodal approach is advised based upon results of this review ( 2 , 3 , 53 ). There are several large RCTs, aiming to recruit between 154 and 1,560 participants, currently in progress that will continue to strengthen this literature base ( 54 – 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal prehabilitation programs are increasingly implemented into standard care ( 4 ) and a multimodal approach is advised based upon results of this review ( 2 , 3 , 53 ). There are several large RCTs, aiming to recruit between 154 and 1,560 participants, currently in progress that will continue to strengthen this literature base ( 54 – 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…46 Recent studies have shown that prehabilitation leads to a reduction of postoperative complications and a faster recovery after surgery. 47 Studies are ongoing in the autologous breast reconstruction setting to determine whether “prehab” targeting of the shoulders, arms, and abdomen to increase range of motion and strength improves postoperative reconstruction outcomes. 48 Prehabilitation is an evolving therapy that seems to be beneficial to breast cancer patients and can help with their overall health, strength, mobility along with an improved sense of self.…”
Section: Prehabilitationmentioning
confidence: 99%
“…Gerade die "nichtchirurgischen Komplikationen" nach einer Operation steigen mit einem Alter > 75 Jahre [15] deutlich an. Es muss daher ein besonderes Augenmerk auf die Prähabilitation [16] und das postoperative Prozedere (ERAS -Enhanced Recovery After Surgery) gelegt werden. Dazu gehören insbesondere eine verbesserte Mobilisation und Atemtraining vor der Operation, ein minimalinvasives Operationsverfahren und ein multimodales Konzept nach der Operation [17].…”
Section: Chirurgische Therapieunclassified